Permutation Flowshop Scheduling in ED Aluminium Using Metaheuristic Approaches - Haposan Vincentius Manalu; Fatiha Widyanti; Nur Mayke Eka Normasari; Andiny Trie Oktavia; Achmad Pratama Rifai (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2023)
This study proposes metaheuristics to solve the permutation flowshop scheduling problem in ED Aluminium which produces kitchen utensils. The aim is to find the processing sequence of products that results in the shortest total completion time, minimizing makespan and total flowtime. Three metaheuristics are developed, which are Simulated Annealing (SA), Large Neighborhood Search (LNS), and Ant Colony Optimization (ACO). Experiments are performed in this research to evaluate the three algorithms. The result using the simulated annealing algorithm is considered better because it has a shorter makespan. The contribution of this study is developing Simulated Annealing, Large Neighborhood Search, and Ant Colony Optimization to solve the problem.